Chronic Marijuana Use and Chronic Obstructive Pulmonary Disease: A Case Report - Ostertag BS; Hendrickson KW (International Journal of COPD, 2025)
Brenna S Ostertag,1 Kathryn W Hendrickson2 1Internal Medicine Department, Providence Portland Medical Center, Portland, OR, USA; 2Division of Pulmonary, Critical Care & Sleep Medicine, The Oregon Clinic, Portland, OR, USACorrespondence: Kathryn W Hendrickson, Division of Pulmonary, Critical Care & Sleep Medicine, The Oregon Clinic, 1111 NE 99th Ave #100, Portland, OR, 97220, USA, Email kwhendrickson00@gmail.comAbstract: Marijuana smoking has become increasingly common in the United States and the world as more states and countries have legalized it for medical and recreational use. There are a number of carcinogens in marijuana smoke similar to those in tobacco smoke, and yet it has been difficult in the literature to find a causal relationship between marijuana smoking and chronic obstructive pulmonary disease (COPD). We present a patient whose main risk factor for emphysema is daily marijuana smoking for upwards of 35 years with no personal history of smoking tobacco, and no other obvious risk factors. Current studies have shown association with chronic marijuana smoking and various lung complaints, forced expiratory volume in 1 second (FEV1) to forced vital capacity (FVC) ratio, and inconsistently with chronic bronchitis. With this case, we add to the current body of literature that suggests a possible relationship between long-term, heavy marijuana use and COPD.Keywords: carcinogens, chronic obstructive pulmonary disease, emphysema, marijuana, smoking